Qualitative Perspectives from African American Youth and Caregivers for Developing the Families Improving Together (FIT) for Weight Loss Intervention - Kitzman-Ulrich, Heather E. (Clin Pract Pediatr Psychol, 2016)
This study obtained qualitative data from African American (AA) youth and caregiver dyads to inform the Families Improving Together (FIT) for Weight Loss Trial. Focus groups were conducted with 55 AA parent and caregiver dyads to gather perspectives on facilitators and barriers, motivators, and program preferences for health and weight loss using a socio-ecological framework. Four main themes emerged: using a positive health promotion framework for weight loss programs, social support and the role of parents in providing positive support, using a socio-ecological approach to examine factors that contribute to weight, and creating programs that are convenient, fun, and reduce barriers to participation. The findings from this study were used to develop the FIT intervention and indicate important individual, interpersonal, and environmental factors to consider when developing weight management and healthy lifestyle programs for AA families.